Identification of Thrips palmi Karny (Thysanoptera: Thripidae) in cucurbit crops in Panama. - Herrera-Vásquez, José Ángel (2013)
The objective of this work includes the morphological and molecular identification of T. palmi in cucurbit crops in Panama. The specimens were collected from the provinces of Los Santos, Herrera, Coclé, Veraguas and Chiriquí, from February 17th of 2009 until August 17th of 2010. The insects identification was realized at the Laboratory of Plant Protection (LPV), of Agricultural Research Center Central (CIAC), of Agricultural Research Institute of Panama (IDIAP), located in Los Canelos, Santa María district, Herrera province, Panama. The specimens were identified by morphology using the taxonomic keys. The polymerase chain reaction (PCR) was used with T. palmi specific-primers, which amplify the mitochondrial gene cytochrome oxidase subunit I (mtCOI). Amplicons (PCR products) of the expected size (220-bp) were obtained from T. palmi. Furthermore, an amplified product was purified and sequenced. To verify the identity of the insect, the sequence obtained from it was analyzed using the Basic Local Alignment Search (BLAST) and compared with reference sequences from the National Center for Biotechnology Information (NCBI)